THE IMPROVING STUDENT LEARNING OUTCOMES COUNTING IN DIVISION OF TWO NUMBERS THROUGH THE IMPLEMENTATION OF THE DIRECT INSTRUCTION LEARNING MODEL IN CLASS IV AT MUHAMMADIYAH 1 LIMBOTO PRIMARY SCHOOL: IMPROVING STUDENT LEARNING OUTCOMES COUNTING IN DIVISION OF TWO NUMBERS THROUGH THE IMPLEMENTATION OF THE DIRECT INSTRUCTION LEARNING MODEL - A Suleman, Nurjana; Anwar, Herson; Nadjamuddin, Asriyati (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Abstract This study aims to improve students' learning outcomes on the topic of division operations involving two-digit numbers through the application of the Direct Instruction Learning Model in Class IV at SD Muhammadiyah I Limboto. The research employs a Classroom Action Research design, consisting of pre-cycle, cycle 1, and cycle 2 stages. Each stage includes planning, action, observation, and reflection. The study was conducted at SD Muhammadiyah I Limboto with 19 students, and the minimum competency criterion (KKTP) was set at 75. Data collection techniques included observation, tests, and documentation. Data analysis was performed using simple formulas to calculate average scores and percentages. The results indicated that in the pre-cycle, 7 students (37%) achieved learning completeness. In cycle 1, this increased to 12 students (63%), and in cycle 2, it further increased to 18 students (95%). The class average in cycle 2 was 86%, surpassing the KKTP of 75. After completing the two cycles, it is evident that the Direct Instruction model significantly improved students' learning outcomes in the arithmetic operation of division involving two-digit numbers. Keywords: Learning Outcomes, Mathematics, Direct Instruction.